Chiral Spirocyclic Phosphoric Acids and Their Growing Applications. Issue 4 (29th March 2021) - Lin, Xufeng; Wang, Lei; Han, Zhao; Chen, Zhouli
Abstract: Chiral spirocyclic phosphoric acids (SPAs) are introduced in 2010 and have been versatile catalysts capable of promoting a wide range of asymmetric organocatalytic reactions, such as multi‐component reactions, Friedel–Crafts reactions, Pictet–Spengler reactions, Fischer indolizations, cycloaddition reactions, desymmetrization reactions, dearomatization reactions, conjugate addition reactions and rearrangement reactions, etc . Moreover, a diverse range of applications in metal‐organic cooperative catalysis, organic photoredox catalysis, total synthesis, materials science and molecular recognition are beautifully illustrated. This account summarizes the past decade's advances in this field and highlights the selected but not comprehensive significant achievements. What is the most favorite and original chemistry developed in your research group? Developing SPINOL‐phosphoric acids (SPAs), TM‐SPINOL‐phosphoric acids (SPAs 2.0) and PCP‐derived planar chiral phosphoric acids (PPAs) for asymmetric catalysis. What is the most important personality for scientific research? Curiosity, optimism, self‐confidence and persistence. What's your hobbies? What's your favorite book(s)? I enjoy cooking. My favorite book is Journey to the West . Who influences you mostly in your life? My mother. What is your favorite journal(s)? The journals publishing the original and systematic work of synthetic chemistry. Could you please give us some advices on improving Chinese Journal of Chemistry? Fast review, fast publication, fast promotion via new media. Abstract : Chiral spirocyclic phosphoric acids are versatile catalysts capable of promoting a wide range of organocatalytic reactions, and also illustrate broad applications in metal‐organic cooperative catalysis, organic photoredox catalysis, total synthesis, materials science and molecular recognition.